Cyanamide Potentiates the Ethanol-Induced Impairment of Receptor-Mediated Endocytosis in a Recombinant Hepatic Cell Line Expressing Alcohol Dehydrogenase Activity - Dahn L. Clemens; Dean J. Tuma; Carol A. Casey (International Journal of Hepatology)
Ethanol administration has been shown to alter receptor-mediated endocytosis in the liver. We have developed a recombinant hepatic cell line stably transfected with murine alcohol dehydrogenase cDNA to serve as an in vitro model to investigate these ethanol-induced impairments. In the present study, transfected cells were maintained in the absence or presence of 25 mM ethanol for 7 days, and alterations in endocytosis by the asialoglycoprotein receptor were determined. The role of acetaldehyde in this dysfunction was also examined by inclusion of the aldehyde dehydrogenase inhibitor, cyanamide. Our results showed that ethanol metabolism impaired internalization of asialoorosomucoid, a ligand for the asialoglycoprotein receptor. The addition of cyanamide potentiated the ethanol-induced defect in internalization and also impaired degradation of the ligand in the presence of ethanol. These results indicate that the ethanol-induced impairment in endocytosis is exacerbated by the inhibition of aldehyde dehydrogenase, suggesting the involvement of acetaldehyde in this dysfunction.